2016
DOI: 10.1055/s-0036-1581099
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Radial Osteotomy for the Treatment of Kienböck Disease

Abstract: Background Kienböck disease is an aseptic necrosis of the lunate of unknown etiology, prevalent in young adults. Treatment aims to lower forces on the lunate, decrease pain and improve function. We conducted a retrospective evaluation of the 10-year clinical and radiological outcomes of radial osteotomy as a treatment for Kienböck disease. Materials and Methods We analyzed pain, grip strength, wrist range of motion (ROM), radiological carpal geometry, and staging of osteoarthritic changes over a 10-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The current techniques for regenerating vascular flow, termed vascularized bone grafting methods, are the mainstream therapies for advanced Kienböck disease. [2,3] Multiple short-term [4] or mid-term [5] clinical trials have reported the usefulness of vascularized bone grafting in patients with advanced Kienböck disease; meanwhile, few long-term clinical results are available, [6] with follow-up no longer than 15 years. Since the first report of Saffar [7] on Kienböck disease treatment with vascularized os pisiform transferring (VOPT), the procedure has become a useful approach for treating Kienböck disease affecting the wrist, due to its ability to relieve pain, improve grip strength, and enhance the range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…The current techniques for regenerating vascular flow, termed vascularized bone grafting methods, are the mainstream therapies for advanced Kienböck disease. [2,3] Multiple short-term [4] or mid-term [5] clinical trials have reported the usefulness of vascularized bone grafting in patients with advanced Kienböck disease; meanwhile, few long-term clinical results are available, [6] with follow-up no longer than 15 years. Since the first report of Saffar [7] on Kienböck disease treatment with vascularized os pisiform transferring (VOPT), the procedure has become a useful approach for treating Kienböck disease affecting the wrist, due to its ability to relieve pain, improve grip strength, and enhance the range of motion.…”
Section: Introductionmentioning
confidence: 99%